2016
DOI: 10.1111/aogs.12843
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal administration of vaginal progesterone and frequency of uterine contractions in asymptomatic twin pregnancies

Abstract: Overall, progesterone does not influence the frequency of uterine contractions in twin pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
3
1
Order By: Relevance
“…A prospective cohort involving 341 patients with CL measurement between 18 and 21 weeks, described CL mean (31.95-33.46 mm) with 68.2% of PTB < 37 weeks. 14 However, when compared with an Italian cohort study that involved 904 twin gestations with a slightly higher CL median (35.4 vs. 38 mm), our study presented a considerably higher incidence of PTB (PTB < 32 weeks, 14.6 vs. 8.3%), which raises the possibility that other factors could be more important to influence the preterm delivery rate in twins, especially when we consider different populations. 15 Thus, before defining what is a short cervix (and its association with sPTB) in a Brazilian twin population it is crucial to know the CL distribution curve in this specific subset of women.…”
Section: Discussioncontrasting
confidence: 58%
“…A prospective cohort involving 341 patients with CL measurement between 18 and 21 weeks, described CL mean (31.95-33.46 mm) with 68.2% of PTB < 37 weeks. 14 However, when compared with an Italian cohort study that involved 904 twin gestations with a slightly higher CL median (35.4 vs. 38 mm), our study presented a considerably higher incidence of PTB (PTB < 32 weeks, 14.6 vs. 8.3%), which raises the possibility that other factors could be more important to influence the preterm delivery rate in twins, especially when we consider different populations. 15 Thus, before defining what is a short cervix (and its association with sPTB) in a Brazilian twin population it is crucial to know the CL distribution curve in this specific subset of women.…”
Section: Discussioncontrasting
confidence: 58%
“…A number of studies with small sample sizes have suggested that progesterone use in singleton pregnancies in women with a history of preterm birth, or a short cervix, can be effective in reducing the risk of preterm labor, provided onset of labor has not occurred at doses ranging from 100 to 400 mg/d from mid-gestation onward. [4][5][6][7][8][9][10] Once arrested preterm labor begins, progesterone is no longer effective at delaying birth. 2,3,11 Recently, a large double-blind, placebo-controlled trial known as the OPPTIMUM trial with 587 neonates in the placebo versus 589 in the progesterone groups showed that there was no effect of vaginal progesterone on gestational age at the time of delivery in singleton pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…12 Similarly, the PREDICT trial, also double blind and placebo controlled, found that vaginal progesterone treatment had no effect on preterm delivery in twin pregnancies, which is in line with previous studies in twin studies. 10,13 Prophylactic use of progestogens during pregnancy continues to be popular, despite the conflicting results from previous trials and the lack of knowledge regarding the effects on the unborn fetus, in particular the effects on fetal steroid profiles. In vivo cholesterol is metabolized into pregnenolone and then into progesterone by the enzymes p450scc and 3b-hydroxysteroid dehydrogenase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation